LOCAL CULTURAL VALUES IN TECHNOLOGY: YOUTUBE TRANS7 AS EDUCATIONAL INFRASTRUCTURE AND ITS USE INDONESIAN LANGUAGE LEARNING - Rakhmadi, Taufik; Suwandi, Sarwiji; Rakhmawati, Ani (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Education in modern era encourages all of us to be able to elaborate on the learning process through various means and facilities including technology. One of the elements that needs to be presented is local cultural elements that contain character education. This research aims to explain the use of teaching materials that represent local cultural values on the Youtube Edutaiment / Magazine Show Trans7 channel as the development of Indonesian language teaching materials. The research method used is qualitative research with a content analysis approach. The data analysis technique using content analysis techniques consists of six steps, namely: (1) data collection, (2) sample determination, (3) recording/transcripting video content, (4) data reduction, (5) drawing conclusions, and ( 6) description/results of analysis of local cultural values in YouTube video. Data validation uses Miles and Huberman's theory, namely data reduction, data presentation, and data verification through Forum Group Discussion (FGD). Based on good algorithm findings, the average number of viewers is 29.5% males aged 13-17 years, and 6.8% of viewers are females aged 13- 17 years. The local cultural values found from the analysis are: (1) The nature of human life, (2) Human relationships with natural resources, (3) Human perception of time, (4) Arts and crafts, (5) Social relationships. Based on these findings, the Youtube Edutainment/MagazineShow Trans7 channel is suitable for use as alternative teaching material and digital means to instill cultural values integrated with education is right step because apart from instilling character, it also instills cultural values in Indonesia. Keywords: Cultural Values, Technology, Youtube, Learning, Indonesian